The professional practice of the primary health care specialist and his role in nutrition education - Mirian Belkis Nápoles Valdés; Felipe Machuca-Contreras; Alfredo Puican Carreño; Juan Carlos Granados Barreto (Revista Información Científica)
Introduction: the primary health care system in Cuba is based on a preventive and community approach. It is based on well-established guidelines and principles with emphasize on the importance of nutrition education at all stages of life, from childhood to adulthood.